A Bibliometric Analysis on Teacher Mindfulness - Ferudun Sezgin; Ziyaeddin Halid İpek (e-Kafkas Eğitim Araştırmaları Dergisi)
With the surge in publications on mindfulness in recent years, there has been a significant increase in studies focusing on teacher mindfulness; thus, teacher mindfulness has emerged as an important research topic and a priority field of study. This bibliometric research employed science mapping tools to analyze Web of Science (WoS) indexed journal publications centered on teacher mindfulness. This review aims to trace the evolution of research in the field of teacher mindfulness over the past two decades. An examination of 165 publications revealed that interest in teacher mindfulness has grown substantially since 2016. The results also provide to the most influential scientists in the field, highlighting the authors' countries of origin, collaborative efforts between countries, and global co-reference networks. A keyword analysis was incorporated into the study to showcase current trends in teacher mindfulness research. Recommendations are provided to inform policy development on teacher mindfulness and to set a direction for future research.